Assessing energy performance of bio-based succinic acid production using LCA. (15th December 2016) - Moussa, Hassan I.; Elkamel, Ali; Young, Steven B.
Abstract: Bio-succinic acid (bio-SAC) is a promising industrial alternative to the currently used petroleum counterparts. This is mainly due to its energy and environmental performances, which were both, assessed using a cradle-to-gate LCA approach. The foreground data used in this LCA were based on real production data from a facility in Louisiana, USA that uses a non-food crop feedstock. Results indicate that electricity use and heat generation were identified to have the biggest impact on the energy and environmental performances of bio-SAC and to have the highest improvements potential. In addition, bio-SAC has lower GWP and non-ren CED values in comparison to petroleum-based SAC by 385% and 1045%, respectively. Scenario analyses indicate that using an energy intensive feedstock (e.g., dextrose) instead of sorghum will have an adverse impact on bio-SAC GWP and non-ren CED. Highlights: An LCA assessment of a promising chemical building block produced using a non-food (energy) crop. The study presents an alternative feedstock for industrial applications without compromising economic and human welfare. The study identifies the hotspots and discusses the potential areas of improvements, find cleaner and more sustainable production processes. Findings can be used as a guideline for decision-making process during the design process of other biochemicals and biofuels.